Profile of ectoparasites and biometric condition of snakehead (Channa striata Bloch 1793) collected from different habitats - Ilham Zulfahmi; Feizia Huslina; Rizki Nanda; Firman M Nur; Rian Djuanda; Suraiya Nazlia; Adli Waliul Perdana (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Studies related to the comparison of ectoparasites that infect snakehead from different habitats and their relationship to biometric conditions have not been widely studied. Thus, present study aimed to investigate the prevalence, intensity, dominance, and predilection of ectoparasites on snakehead collected from ditches, paddy fields, and swamps and correlate them with biometric conditions. In total of 90 snakehead fish were collected from ditches, paddy fields, and swamps. The observation of ectoparasites was performed on the gills, fins, and skin. The parameters measured in this study were ectoparasite profiles and biometric condition of fish. Specifically, the parameters of the ectoparasite profile included prevalence, intensity, dominance, and predilection. Meanwhile, the parameters of the biometric conditions were the length-weight relationship, the distribution of length and weight classes, and condition factors. Five species of ectoparasites that have been identified as Tetrahymena sp., Epistylis sp., Trichodina sp., Dactylogyrus sp., and Gyrodactylus sp. Tetrahymena sp. infection in snakehead was reported for the first time. The ditch habitat had the highest prevalence and intensity, which were 76.7% and 15.4 ectoparasites/fish, respectively. Tetrahymena sp. and Epistylis sp. were detected in sneakhead from all habitats, Trichodina sp. was detected at ditch and paddy field habitats, whereas, Gyrodactylus sp. and Dactylogyrus sp. were only found in swamp habitats. The gill was the predilection organ that most vulnerable to ectoparasite infection. Infected Snakehead tend to have lower average weight and length than healthy snakehead. Snakehead with a weight range of 115.2-145.2 g and a length range of 258.5-268.5 mm tend to be more vulnerable to ectoparasite infection compared to other sizes.Keywords:Tetrahymena sp.PrevalenceIntensityPredilectionLength-weight relationship